Loxhd1b inhibits the hair cell development in zebrafish: Possible relation to the BDNF/TrkB/ERK pathway - Liu, Jingwen; Zhang, Xu; Zhang, Qingchen; Wang, Rongrong; Ma, Jingyu; Bai, Xiaohui; Wang, Dawei (Frontiers in Cellular Neuroscience, 2022)
Mutations in lipoxygenase homology domain 1 (Loxhd1) cause autosomal recessive inheritance, leading to high-frequency and intermediate-frequency hearing losses in patients. To date, studies on the localization of Loxhd1 gene expression are limited. In this study, we aimed to observe the expressions of Loxhd1b in zebrafish, C57BL/6 murine cochlea, and HEI-OC1 cells. Results of the in situ hybridization with zebrafish embryos at different time points showed that Loxhd1b was expressed in zebrafish at the inner ear and olfactory pores, while the immunostaining showed that Loxhd1b was expressed in both C57BL/6 mouse cochlea and HEI-OC1 cells. Immediately after the injection of morpholino, the impact of Loxhd1b on the development of zebrafish’s hearing and balance functions was evaluated based on immunohistochemistry, startle response. The results of transcriptomics analysis revealed the downstream molecule BDNF and verified that Loxhd1b inhibited the development of zebrafish hair cells through the BDNF/TrkB/ERK pathway based on western blotting, immunostaining, and rescue experiments. This was the first time that the BDNF/TrkB/ERK pathway was identified to play a critical role in the molecular regulation of the development of zebrafish hair cells and the auditory development by Loxhd1b.